Interleukin (IL) 18 and Its Relation with Diabetes Mellitus and Chronic Periodontitis - Kavitha J (Journal of Global Pharma Technology, 2020)
IL-18 is a member of the IL-1 family of cytokines. IL-18 demonstrates a unique function by binding to a specific receptor expressed on various types of cells. Interleukin (IL)-18 was originally discovered as a factor that enhanced IFN-γ production from anti-CD3-stimulated Th1 cells, especially in the presence of IL-12. Diabetes mellitus is a group of metabolic diseases characterized by chronic hyperglycemia resulting from defects in insulin secretion, insulin action, or both. Metabolic abnormalities in carbohydrates, lipids, and proteins result from the importance of insulin as an anabolic hormone. Chronic periodontitis, also known as adult periodontitis, is an infectious inflammatory disease caused by the bacteria of the dental plaque, resulting in the progressive destruction of the tissues that support the teeth, i.e. the gingival, the periodontal ligament, cementum, and the alveolar bone. Chronic periodontitis can also play a role as a metabolic stress or for diabetes control. In this review article, we will focus on the unique features of Interleukin (IL) 18 and its relation with diabetes mellitus and chronic periodontitis.